Keberkesanan sistem anggaran kos yang dipraktikkan oleh jurukur bahan di Malaysia - Ismail, Noor Akmal Adillah (2005)
The aim of the study is to identify the current estimating system used by Quantity Surveying firms in Malaysia in aspect to identify the effectiveness of the current estimating system practiced by Quantity Surveying firms in Malaysia. Also studied are the problems faced by the Quantity Surveyors (QS) and also methods to minimize the problems faced and the effectiveness of the system. The methodology that has been used to execute the study includes literature review and data collection through questionnaires survey. The result of the study shows that the current estimating system is effective but there are some persisting problems that need improvements. The main problem faced by QS related to the non existence of a standard system that can support the QS in understanding the client’s requirements. The study also found that the most important aspect that can help to improve the existing estimating system is by ensuring that the QS must always be furnished with adequate information regarding the project